Pengaruh Lama Waktu Penyimpanan dan Penyinaran Cahaya Terhadap Komponen Penyususn Minyak Atsiri dari Tanaman Sereh (Cymbopogon winterianus) serta Uji Aktivitas Menggunakan Metode BSLT (Brine Shrimp Lethality Test) - Pratiwi, Rahmania Tulus Setya; Iftitah, Elvina Dhiaul; Ulfa, Siti Mariyah (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
This research concerned with the effect of storage time and light radiation toward the composition of essential oil from lemongrass. The activity of  lemongrass oil before and after storage was examined using BSLT. The storage condition were performed in clear vials and black vials and then placed in wooden box in three different conditions for 6 weeks. The first box was radiated with the lamp for 24 hours, the second box made from a transparent material at front and it back sides, and the third was a closed-black box. Analysis of the component of essential oil before storage using Gas Chromatography-Mass Spectrometry (GC-MS) and after storage using Gas Chromatography (GC). The results from GC-MS showed that the percentage of citronellal, which is the active compound of lemongrass oil,is 24.730% before storage and significantly increased to 29.195% after 2 weeks in clear vials (box 1). The activity test of this sample was conducted using BSLT. The LC50 values of lemongrass oil before storage is 9.19 ppm and changing to 19.76 ppm after storage. Keywords : Brine Shrimp Lethality Test, citronellal, essential oil, light radiation, storage